Crescita e struttura dello scheletro di Savalia savaglia (Bertoloni, 1819) (Anthozoa, Zoanthidea) - Canessa, Martina; Bo, Marzia; Trainito, Egidio; Bavestrello, Giorgio (Biologia Marina Mediterranea, 2025)
The zoanthid Savalia savaglia is known for its aptitude of growing on the skeleton of gorgonians after destroying the host coenenchyme. This charismatic species has been the subject of numerous studies on its geographical distribution, ecological role, reproductive biology, age, and conservation. In this research, we describe the growth of the skeleton based on large dead specimens found in the Tavolara MPA (NW Sardinia). Using cross-sections of the skeleton, it is readily evident that the large specimens result from the coalescence of different colonies, each infesting a different gorgonian. The skeleton ultrastructure allowed the recognition of a laminar architecture of organic material characterised by numerous small spines stacked on each other, layer by layer, cementing one skeletal lamina to the next. This organisation is probably at the base of the efficient mechanical properties of S. savaglia.